The Effect of Product Attributes, Brand Image, and Variety Seeking on Brand Switching of Lemonilo Instant Noodles - Achmad Jauhar Wiyoko; Ralina Transistari (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2024)
This study aims to analyze the effect of product attributes, brand image, and variety-seeking behavior on brand switching from other brands to Lemonilo instant noodles. This research is quantitative, utilizing a non-probability sampling method and purposive sampling technique. The sample size of this study consists of 100 respondents. The analytical method used is multiple linear regression analysis. Research results show that product attributes, brand image, and variety seeking have a positive effect on brand switching from other brands to Lemonilo instant noodles.